Do we need a new science-policy interface for food systems? - Turnhout, Esther; Duncan, Jessica; Candel, Jeroen; Maas, Timo Y.; Roodhof, Anna M.; DeClerck, Fabrice A.J.; Watson, Robert T. (American Association for the Advancement of Science, 2021)
Credibility, legitimacy, and diversity of knowledge are critical